Performance, diversity analysis and character association of black pepper (Piper nigrum L.) accessions in the high altitude of Idukki district, Kerala - T Sathyan, M K Dhanya, M Murugan, T T Preethy, T S Aswathy, (Journal of Spices and Aromatic Crops, 2018)
The experiment was conducted to evaluate black pepper accessions for growth parameters, yield attributing characters and yield. Out of the ten accessions tested, Karimunda recorded the highest fresh (1.61 kg) and dry (508.7 g) yield of berries plant-1. Fresh weight showed significant positive genotypic correlation to dry weight and while negative correlated to 100 berry volume, 100 berry weight and number of berries spike-1. Hence, selection based on number of berries spike-1, 100 berry volume and 100 berry weight may not lead to the high yielding black pepper variety. The results showed that Karimunda is the most suitable black pepper variety for high altitude areas of Idukki district.